Analisis Daya Saing Produk Ekspor Indonesia Sebagai Strategi Wirausaha Memasuki Pasar Australia - Widyantini, Rahayu (Cendekia Niaga, 2021)
The trade cooperation between Indonesia and Australia opens a new chapter with the ratification of the existing comprehensive economic cooperation agreement. This opportunity must be maximally utilized by Indonesian export entrepreneurs by looking at the potential of Indonesian products in the Australian market. The purpose of this study is to analyze the characteristics needed by export entrepreneurs and to analyze the potential of Indonesian products and their requirements in the Australian market which are used as a reference for export entrepreneurs entering the Australian market. The method used in this research is a mix method with descriptive analysis of export entrepreneurial behavior and with quantitative data processing to see the competitiveness of Indonesian products in the Australian market using the value of Revealed Comparative Advantage (RCA). Export entrepreneurs must have mental characteristics and export knowledge skills. Export knowledge about the competitiveness of Indonesian products is obtained from the results of RCA calculations, namely products that have high potential in the Australian market, including Raw materials, Food Products, Minerals, Fuels, Food, Textiles and Clothing, Textiles, Intermediate goods, Consumer goods and Ores and Metals. Apart from seeing the potential of Indonesian products in the Australian market, Indonesian export entrepreneurs need to also look at export and entry requirements in Australia